2012
DOI: 10.1111/j.1365-2265.2012.04359.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sex hormones and C‐reactive protein in healthy chinese men

Abstract: We have confirmed the association of androgens with reduced inflammation as measured by CRP in Chinese men. This is independent of conventional cardiovascular risk factors and is explained in part by markers of central obesity and insulin resistance, rather than metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
(77 reference statements)
4
24
2
1
Order By: Relevance
“…Consistent with other observational studies serum testosterone was negatively associated with some markers of inflammation (Bonithon-Kopp et al, 1988;Brand et al, 2012;Gannage-Yared et al, 2011;Haring et al, 2012;Kupelian et al, 2010;Laaksonen et al, 2003;Yang et al, 1993;Zhang et al, 2013). This study adds by considering an additional biomarker of androgen activity, AAG, which was not associated with lower values of any of the inflammatory markers considered, but was associated with higher fibrinogen as well as with hemoglobin as would be expected of an androgen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with other observational studies serum testosterone was negatively associated with some markers of inflammation (Bonithon-Kopp et al, 1988;Brand et al, 2012;Gannage-Yared et al, 2011;Haring et al, 2012;Kupelian et al, 2010;Laaksonen et al, 2003;Yang et al, 1993;Zhang et al, 2013). This study adds by considering an additional biomarker of androgen activity, AAG, which was not associated with lower values of any of the inflammatory markers considered, but was associated with higher fibrinogen as well as with hemoglobin as would be expected of an androgen.…”
Section: Discussionsupporting
confidence: 91%
“…The available evidence from these RCTs generally shows little effect of testosterone therapy on CRP (Aversa et al, 2010;Frederiksen et al, 2013;Kapoor et al, 2007;Nakhai-Pour et al, 2007;Ng et al, 2002), white blood cell count (Kalinchenko et al, 2010) or fibrinogen (Smith et al, 2005), although one RCT reported testosterone decreased CRP (Kalinchenko et al, 2010) among a subset of men. Larger observational studies among men usually, but not always, report serum testosterone inversely associated with CRP (Gannage-Yared et al, 2011;Haring et al, 2012;Kupelian et al, 2010;Laaksonen et al, 2003;Nakhai Pour et al, 2007;Zhang et al, 2013), white blood cell counts and/or its differentials (Brand et al, 2012;Haring et al, 2012;Tang et al, 2007) and fibrinogen (Bonithon-Kopp et al, 1988;Haring et al, 2012;Yang et al, 1993). Experimental and observational evidence may differ for a number of reasons: the small size of most RCTs of testosterone therapy, differences in the action of exogenous and endogenous testosterone, serum testosterone acting as a marker of health status or serum testosterone not capturing all androgen activity (Labrie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that testosterone levels in men are inversely associated with C-reactive protein (CRP) (Kupelian et al, 2010; Tsilidis et al, 2013; Zhang et al, 2012). Even in young men, clinically low testosterone levels are associated with increased expression of TNFα and other inflammatory factors (Bobjer et al, 2013).…”
Section: Mechanisms Underlying Sex Differences In Obesity and Alzhmentioning
confidence: 99%
“…Two randomized controlled trials of androgen replacement therapy in hypogonadal men reported a decrease in the concentration of pro-inflammatory cytokines in the active therapy arm (Malkin et al 2004; Kalinchenko et al 2010), but other trials did not confirm these findings (Ng et al 2002; Singh et al 2002; Kapoor et al 2007; Nakhai-Pour et al 2007). A few epidemiologic studies have evaluated the cross-sectional association between sex steroid hormones and inflammatory biomarkers in men, but had inconsistent results (Laaksonen et al 2003; Van Pottelbergh et al 2003; Bhatia et al 2006; Maggio et al 2006; Nakhai Pour et al 2007; Tang et al 2007; Maggio et al 2009; Schneider et al 2009; Kaplan et al 2010; Kupelian et al 2010; Brand et al 2012; Zhang et al 2012). Moreover, some of the latter studies did not adjust for important confounders (e.g., smoking and obesity) (Laaksonen et al 2003; Van Pottelbergh et al 2003; Bhatia et al 2006; Tang et al 2007; Kaplan et al 2010), and very few studies mutually adjusted for other sex hormones (Nakhai Pour et al 2007; Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A few epidemiologic studies have evaluated the cross-sectional association between sex steroid hormones and inflammatory biomarkers in men, but had inconsistent results (Laaksonen et al 2003; Van Pottelbergh et al 2003; Bhatia et al 2006; Maggio et al 2006; Nakhai Pour et al 2007; Tang et al 2007; Maggio et al 2009; Schneider et al 2009; Kaplan et al 2010; Kupelian et al 2010; Brand et al 2012; Zhang et al 2012). Moreover, some of the latter studies did not adjust for important confounders (e.g., smoking and obesity) (Laaksonen et al 2003; Van Pottelbergh et al 2003; Bhatia et al 2006; Tang et al 2007; Kaplan et al 2010), and very few studies mutually adjusted for other sex hormones (Nakhai Pour et al 2007; Zhang et al 2012). Therefore, the aim of this study was to investigate the cross-sectional association between endogenous sex steroid hormones (total testosterone, calculated free testosterone, total estradiol, calculated free estradiol and androstanediol glucuronide, a metabolite of dihydrotestosterone), sex hormone binding protein (SHBG) and biomarkers of inflammation (CRP and white blood cell count [WBC]) in a large nationally representative sample of US men after carefully adjusting for all important confounders.…”
Section: Introductionmentioning
confidence: 99%